Florida Biosolids: Management and Land Application Rules - John Hallas; Cheryl L. Mackowiak; Ann C. Wilkie (EDIS, 2016)
Biosolids are the liquid, semisolid, and solid fractions of the treated waste stream from a domestic wastewater treatment facility (WWTF). On August 29, 2010, the Florida Department of Environmental Protection (FDEP) formally adopted its rule for the management of wastewater biosolids, Chapter 62-640, Florida Administrative Code (F.A.C. 2010). This 6-page fact sheet from the Florida Biosolids series covers applicability of the rule, the intent of Chapter 62-640, F.A.C., land application requirements, biosolids storage, cumulative application limits, setback distances, pH, soil depth, runoff prevention, additional application site restrictions for Class B biosolids, NMPs, and special geographic areas. Written by John Hallas, Cheryl L. Mackowiak, and Ann C. Wilkie, and published by the UF Department of Soil and Water Science, October 2015.